Immigrant voices in students' essay texts: Between assimilation and pride. (May 2014) - Archakis, Argiris
The present study concentrates on immigrants' positionings towards the discourse of the majority in Greece. While facing an influx of immigrants during the 1990s, the Greek majority adopted a particularly racist discourse. My purpose here is to explore how immigrant students attending Greek schools attempt to articulate their voice in relation to the assimilationist, racist discourse surrounding them. Focusing on the functions of the disclaimer I am adjusting myself, but … used by immigrant students in a corpus of school essays, we will argue that it constitutes a particularly effective means of allowing them to raise a complex and polyphonic voice pursuing adjustment to the host country, without, however, losing face and pride. More particularly, the data analysis shows that in their school essays, and under the influence of their immigrant/ethnic communities and their negative experiences in the host country, immigrant students recontextualise the majority disclaimer I'm not a racist, but … used by the majority population. The disclaimer seems to have undergone an entextualisation process that has led to the new disclaimer I am adjusting myself, but …, which is intertextually linked with the former, but reversing its target. While the majority disclaimer is an expression of latent racism, the one discussed here involves mitigated threatening acts against majority assumptions as well as the enhancement of immigrant students' face.